Perlindungan Hukum Merek Asing Terdaftar Di Indonesia (Studi Putusan Mahkamah Agung Republik Indonesia Nomor 534 K/Pdt.Sus-HKI/2019) - Azhari AR; Arief Basofi Siregar (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
Abstract Whereas the rejection of a Mark Application according to paragraph (1) letters a to c is regulated by a Ministerial Regulation. Article 21 paragraph (2) letter a regulates the prohibition of having the same mark with the name of a famous person, so the Directorate General must reject the application for registration of a mark that is the same as the name of a well-known person or legal entity. It turns out that the Defendant is the owner of a mark that has been registered in the General Register of Marks at the Directorate General of Intellectual Property No. IDM000285464 protects the types of goods in class 11. The plaintiff feels aggrieved by the registration carried out in Indonesia because it has similarities with the plaintiff's property in Vietnam and several countries. The Cassation Appellant's reasons can be justified, because the Commercial Court at the Central Jakarta District Court has wrongly applied the law, it turns out that the Judex Facti's decision in this case does not contradict the law and / or laws. Keywords: Legal Protection, Foreign Trademarks, Registered, Registration, Trademark Rights Abstrak bahwa penolakan Permohonan Merek menurut ayat (1) huruf a sampai c diatur dengan Peraturan Menteri. Pasal 21 ayat (2) huruf a mengatur larangan persamaan merek dengan nama orang terkenal, maka Direktorat Jenderal harus menolak permohonan pendaftaran merek yang sama dengan nama orang atau badan hukum terkenal. Ternyata diketahui bahwasanya Tergugat adalah pemilik merek yang telah terdaftar dalam Daftar Umum Merek pada Direktorat Jenderal Kekayaan Intelektual No. IDM000285464 melindungi jenis barang dalam kelas 11. Penggugat merasa dirugikan dengan pendaftaran yang dilakukan di Indonesia karena memiliki persamaan dengan milik penggugat di Vietnam dan beberapa negara. Alasan-alasan kasasi dari Pemohon Kasasi dapat dibenarkan, oleh karena Pengadilan Niaga pada Pengadilan Negeri Jakarta Pusat telah salah menerapkan hukum, ternyata putusan Judex Facti dalam perkara ini tidak bertentangan dengan hukum dan/atau undang-undang. Kata Kunci : Perlindungan Hukum, Merek Asing, Terdaftar, Pendaftaran, Hak Merek